Economic Growth, CO2 Emissions and Electric Consumption: Is there an Environmental Kuznets Curve? An Empirical Study for North America Countries - Rosado Anastacio, Joel Alejandro (International Journal of Energy Economics and Policy, 2017)
The goal of this paper is validity the environmental Kuznets curve (EKC) hypothesis for north America countries (Canada, United States and Mexico) over the annual period 1980–2008. Pedroni cointegration tests are applied for testing long-run relationship between the variables. Using the panel fully modified ordinary least squares (FMOLS) and the panel dynamic ordinary least squares (DOLS) determinate the elasticities of the long-run relationships. The results show that there is an inverted U-shape relationship. Finally, in the long-run, the results of the causality test show that there is a unidirectional causal flow from energy consumption, electricity consumption and economic growth to CO2 emissions in North America. Keywords: Environmental Kuznets Curve, Carbon Dioxide Emissions, Economic Growth. JEL Classifications: C33, Q4, Q43, Q56